PEMBERDAYAAN IBU-IBU PKK DALAM PELATIHAN PEMBUATAN DECOUPAGE BERBASIS INDUSTRI KREATIF - Marhaini; Mardwita; Wisudawati, Nidya; Patradhiani, Rurry; Hastarina, Merisha (Jurnal Abdimas Musi Charitas, 2021)
This training aims to increase the economic independence of housewives in RT 030 RW 007,Kalidoni Village, Palembang. The implementation of this activity is packaged interactively bypresenting lecturers from the Faculty of Engineering, University of MuhammadiyahPalembang. The form of service activities is in the form of decoupage technique training, thistechnique is a technique of beautifying ordinary items into good products, artistic value andhigher selling value. The material used is plain woven bag material which is then decoupagetechnique (from French which means cutting, decorating), affixed with motif tissue paper(napkin) followed by varnishing, will produce a beautiful woven bag. This skill is quite easy butrequires precision and gentleness because the tissue paper used is very smooth and easily torn ifyou are not careful in cutting, pasting and varnishing. Not only training, but in this activity,online business counseling is also held through the marketplace and social media. An effectivesolution for mothers of productive age but do not work outside the home. Overall, theimplementation of activities can provide new business opportunities for housewives.